Multiferroic properties of three-layer Aurivillius compound Bi4TiFeNbO12: A first-principles and experimental study. (October 2020) - Lavado, C.; Rébola, A.F.; Machado, R.; Stachiotti, M.G.
Abstract: We present a first-principles and experimental study of the structural, ferroelectric, and magnetic properties of the potentially multiferroic three-layer Aurivillius compound Bi 4 TiFeNbO12 . This system can be realized by inserting a BiFeO 3 formula unit into the two-layer Aurivilius Bi 3 TiNbO 9 matrix. The calculations are performed using the PBEsol exchange–correlation functional within the DFT+U framework. First we search for potential cation site preference by comparing the relative stability of different Fe, Nb and Ti arrangements. We find a preference for the Fe 3＋ ions to occupy the inner site within the pseudoperovskite block. This configuration exhibits a band gap of 1.2 eV ( U Fe = 4 eV ) and ferroelectric and magnetic orders. A value of 66 μ C/cm 2 is obtained for the spontaneous polarization, which is similar to the one obtained for Bi 4 Ti 3 O12 (BIT). The magnetic ground state of this system is characterized by a strong antiferromagnetic coupling between the Fe 3＋ ions located in the central layer. By mapping to a Heisenberg model, the superexchange antiferromagnetic coupling between nearest-neighbor Fe 3＋ cations is estimated to be J = 53 meV. Finally, we synthesize Bi3.25 La0.75 TiFeNbO12 ceramics by the solid-state reaction method. Their structural, electric and magnetic properties are confronted with the theoretical predictions. Highlights: A novel multiferroic compound with n = 3 Aurivillius structure is presented. The material is realized by inserting BiFeO 3 into a Bi 3 TiNbO 9 matrix. We observe the coexistence of ferroelectric and antiferromagnetic order. Experimental results support theoretical predictions by DFT.